Business Processes Content of Trade Organizations and Peculiarities of their Management in Market Environment - Teplov, Vitaly Ivanovich; Tarasova, Elizaveta Evgenievna; Alyabieva, Marianna Vladimirovna; Isaenko, Elena Viktorovna; Pidoimo, Lyudmila Petrovna (International Review of Management and Marketing, 2016)
The article scrutinizes the peculiarities of the process approach to trade organizations management and provides the authors' definition of business processes. The article singles out several common essential points, which characterize business processes in trade organizations, substantiates the interconnection between main and auxiliary processes. The article substantiates that in trade organizations there can be singled out four types of the main business processes of the first level “Purchase of goods”, “Goods stock regulation”, “Wholesale goods supply” and “Retail goods sales”. The first level business processes of trade organizations were decomposed into smaller business processes; business processes classification was added with the following classification features: by the received effect, by the targeting, by the continuity of execution depending on the level of detailing. The article singles out the second level business processes and examines the directions for the improvement of the main business processes management in trade. It is substantiated that the most important marketing directions of trade organizations' business processes improvement should include: direct improvement of the first level business processes; development of the set of tools of business processes management in trade; and development of the technique of business processes fecundity assessment. According to the authors business processes management in trade organizations should be executed at three levels of management: upper, middle and lower. A conceptual scheme of organization's business processes management has been worked out, which includes feedback information from the executor of the business process to the leader (business process indicators) and from the head to the business process owner (managerial accounting on business process). Keywords: Business processes, trade organizations, business processes management JEL Classifications: M1, O24